IMPLEMENTASI PENGETAHUAN KE AGAMAAN TERHADAP PRILAKU SOCIAL ANAK DI SEKOLSH DASAR ISLAM TIRTAYASA - Ahmad Mubarok; M. Asep Rahmatullah (Jurnal Anak Bangsa, 2022)
Education is a knowledge transformation effort carried out by educators to students to educate the children of the Indonesian nation. Religious education is the first and foremost basis that must be owned by every citizen of the nation, especially the nation's children as the next generation, successor and perfection of the Unitary State of the Republic of Indonesia. In this study the authors used qualitative research with survey methods with a correlational approach which was carried out at SD Islam Tirtayasa Serang Banten by involving students in grades, four, five and six. Data collection is done by observation, interviews, questionnaires, and documentary studies. Data analysis used correlational analysis with the product moment formula correlation technique